A study on the criteria of contractor chosen by client - Nur Afiqah, Awang (2017)
Contractor is an organization or individual who directly employs or engages construction workers or as part of their business carries out, manages or control construction work. Selection of contractor is a crucial part in the process of construction management. It gives big influences upon projects and their successes. [8] On the other hand, it also affect the contractor since they fail during tendering process. Therefore, the decision to tender is the first step that contractors need to consider. [7] The tender price will be influence by the risk factors. The risk has the capacity of eroding profit and moving the project from a profit making into loss-making venture. The contractor that fail to get awarded, generally cannot generate income and slowly effect the company’s reputation. [4] Hence, a study was conducted to determine the criteria of contractors that to be chosen by client. In order to win the tender, the contractor need to better understand the requirement to fulfil the client’s needed. [2] The main objective of this study was to find the factors that influence while selecting the criteria of contractor by client. The study was conducted by sending a questionnaire to respondents, having an industrial visit and conducted an interview session. The respondents involve were 57 persons from client, contractor and developers that registered with CIDB. Therefore, to analyze the data collected, Relative Importance Indices (RII) will be utilized. In this study, three main factors were point out that were in term of experience of the contractor, financial of the contractor and the management of the company. Between these three factors, the result showed that management of the company was the most factor to be chosen by client. As a conclusion, the most chosen criteria of contractor was in term of management of the company. Recommendations were also included in this study to improve the method of selection the best criteria of contractor for any construction project.